Estudo filogeográfico de Micrurus lemniscatus (LINNAEUS, 1758) (SERPENTES: ELAPIDAE) - Abreu, Tatianne Piza Ferrari (2014)
Micrurus lemniscatus is a South American coral snake species, popularly known as “coral verdadeira”. It is widely distributed in Seasonally Dry Forests (SDF), Gallery Forests and Rainforests. The Tertiary events and the climatic oscillations of the Quaternary affected the distribution of these ecosystems altering, in turn, the distribution of animals associated to these habitats. We hypothesize that the forest expansion and contraction cycles caused by climate fluctuations may have influenced the current distribution and genetic structure of M. lemniscatus. This study aimed to study the evolutionary relationships and patterns of divergence among M. lemniscatus lineages and infer the historical biogeographic events that influenced the distribution and genetic variation. Twenty-nine individuals of M. lemniscatus were sampled from 16 localities in the states of Tocantins, Bahia, Goiás, Alagoas, Mato Grosso, Maranhão, Pará and Amazônia. Three mitochondrial regions (COI, 16S and ND4L) were sequenced, and together generated a fragment of 1595 bp and 23 different haplotypes. The analyses showed a very ancient lineage divergence ~ 4.5 Myr and high genetic differentiation among localities (FST=0.932; p<0.01), suggesting a limited gene flow among geographical regions. The demographic analyzes and neutrality tests indicated that there is no sign of expansion and that populations have constant size (Tajima’s D = 0.521; p = 0.763 and Mismatch distribution = 0.009; p= 0.779). In the analysis of the evolutionary relationship between haplotypes (by median-joining network method), no relationship between lineage and geographical space was found, suggesting incomplete lineage sorting. The results corroborate and give evidence that populations of M. lemniscatus were distributed in a more continuous region in the past, and the current distribution of this species may be the result of the reduction and separation of the geographical scope of their distribution, rather than having itself been an expansion event. This may be the result of cycles expansion of SDF and retraction of the rainforests during the cool and dry phases of the Quaternary.